Work and Energy: The Development of Learning Media Based on Smart Apps Creator to Enhance Critical Thinking Skills - Vita Alam Sari; Winda Setya; Adam Malik (CV. Generasi Intelektual Digital (GEN ID), 2024)
This study aims to determine the feasibility of interactive learning media based on Smart Apps Creator, implementation of learning, improvement of students' critical thinking skills, and student responses to the use of interactive learning media based on Smart Apps Creator. The research procedure uses the ADDIE model which includes the analysis, design, development, implementation, and evaluation stages. The research population was all students of class X IPA 4 SMAN 6 Tambun Selatan with a total sample of 30 people. The research instrument used media validation sheets, observation sheets, critical thinking skills tests and student response questionnaires. The results of the study showed that Interactive learning media based on Smart Apps Creator is feasible with an average percentage of 87% including very valid interpretations. The implementation of learning is obtained through observation sheets with an average percentage of 91% which is interpreted very well. The use of interactive learning media based on Smart Apps Creator can improve students' critical thinking skills with an average N-gain of 34.93% including moderate interpretation. The response of students to interactive learning media based on Smart Apps Creator is 81.67%, which includes very interesting interpretations.